Highly Efficient Platinum Free Multi‐Walled Carbon Nanotubes/Silver Nanocomposites as Counter Electrode for Dye Sensitized Solar Cell. Issue 9 (16th June 2016) - Nath, Bikash Chandra; Das, Dhaneswar; Basumatary, Jabbor; Ahmed, Gazi Ameen; Dolui, Swapan Kumar
Abstract: In this report we have synthesized multi‐walled carbon nanotubes (MWCNT)/silver (Ag) nanocomposites using reduction method. Integrating properties of MWCNT and Ag as nanocomposites have shown potential application as counter electrode (CE) in dye sensitized solar cells (DSSCs). Different analyses were performed using Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD) and Raman, analysis to examine the successful incorporation of Ag nanoparticles with MWCNT. A systematic morphological study was carried out using scanning and transmission electron microscopy. The cyclic voltammetry (CV) reveals the enhancement in catalytic activity towards redox couple (I3 − /I − ) in DSSCs. Thus, current density vs voltage ( J‐V ) curve assists in evaluating the influence of Ag nanoparticles on MWCNT during photovoltaic conversion. The optimum photo‐conversion efficiency ( η ) of 5.44 % was achieved using MWCNT/(0.75 %)Ag nanocomposites as CE which is analogous to conventional Pt CE. Finally, electrochemical impedance parameters endorse well in the improvement of photo conversion efficiency through reduction in charge transfer resistance ( Rct ). Abstract : Here, we have synthesized the MWCNT/Ag nanocomposites using reduction method and further applied as counter electrode (CE) in dye sensitized solar cells (DSSCs). The optimum photo‐conversion efficiency ( η ) of 5.44% was achieved using MWCNT/(0.75%)Ag nanocomposites as CE which is analogous to conventional Platinum CE.